Structure of Multi-Stage Composite Genetic Algorithm (MSC-GA) and its performance - Li, Fachao; Xu, Li Da; Jin, Chenxia; Wang, Hong (Expert systems with applications, 2011)
► We propose an improved genetic algorithm named Multi-Stage Composite Genetic Algorithm (MSC-GA). ► The results indicate that the new algorithm possesses several advantages such as better convergence. ► As a result, it can be applied to many large-scale optimization problems that require higher accuracy. In view of the slowness and the locality of convergence for Simple Genetic Algorithm (SGA) in solving complex optimization problems, we propose an improved genetic algorithm named Multi-Stage Composite Genetic Algorithm (MSC-GA) through reducing the optimization-search range gradually, and the structure and implementation steps of MSC-GA is also discussed. Then, we consider its global convergence under the elitist preserving strategy using the Markov chain theory and analyze its performance through three examples from different aspects. The results indicate that the new algorithm possesses several advantages such as better convergence and less chance of being trapped into premature states. As a result, it can be widely applied to many large-scale optimization problems which require higher accuracy.